Complex formation between AmtB and GlnK: an ancestral role in prokaryotic nitrogen control. (1st February 2005) - Javelle, A.; Merrick, M.
Abstract : Ammonium transport proteins belonging to the Amt family are ubiquitous in prokaryotes. In Escherichia coli, the AmtB protein and the associated PII signal transduction protein (GlnK) have recently been recognized as an ammonium sensory system that effectively couples the intracellular nitrogen regulation (Ntr) system to external changes in ammonium availability. Given the almost invariant coupling of AmtB and GlnK in bacteria and archaea it seems probable that these two proteins may constitute an ancestral nitrogen-responsive system that has been coupled with a variety of unrelated nitrogen regulatory processes, which are now found in prokaryotes. The multiplicity of PII proteins could therefore be considered to have evolved from an ancestral GlnK-like protein and to have subsequently been adapted to control many other aspects of nitrogen metabolism.